Upaya Mendukung Diversifikasi Energi Di Lingkungan Kampus Melalui Pengisian Baterai Sepeda Listrik Mandiri Pada PLTS Off-grid Universitas Mataram - Harjian, Muhammad Rivaldi; Adnyani, Ida Ayu Sri; Supriyatna; Natsir, Abdul; Perdana, I Ketut; Putra, R. Reski Eka; Tawaqqal, Akbar (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This Community service aims to design and implement an independent electric bicycle battery charging system using an Off-grid Solar Power Plant (PLTS) in the campus environment of the University of Mataram. The charging system is designed with two models: charging via an inverter using the bicycle's built-in charger and direct charging using a charging box equipped with a boost converter, charging regulator module, Arduino, current and voltage sensors, and LCD. The electric bicycle battery charging test started at 09:40–16:10 WITA. The initial voltage when charging the battery was 44.04 Volts and the initial battery charging current was 5.86 A. The battery charging time was 6.5 hours until the battery voltage reached 49.98 Volts and the total energy required was 681.02 Wh (Watt-hour). Testing was carried out on two charging methods, namely fixed and non-fixed currents, to compare charging efficiency and effectiveness. The test results show that the independent charging system can charge a 48 Volt 12 Ah electric bicycle battery in about 6.5 hours with a total energy of 681.02 Wh. Charging efficiency through the charger box ranges from 80–98%. This system is considered effective in supporting the use of renewable energy and environmentally friendly transportation in the campus environment.